An Integrated Static Reservoir Modelling of Yan Chang formation, Ordos Basin, China - Ong , See Ching (Universiti Teknologi PETRONAS, 2016)
Understanding and applying integrated data in reservoir characterization and static geomodeling is essential in order to visualized and calculate the economic value of a field, in this case Yan Chang, Chang 3 formation. Hence, the main purpose for this project is to use integrated raw data by performing geophysical and petrophysical evaluation for Chang 3 and build a static model. The method used is basic seismic interpretation skill for geophysical evaluation including horizon picking for top and base for Chang 3, regional fault picking, and time depth conversion of the top and base of Chang 3 surfaces generated from the picked horizon. While in petrophyscial evaluation, it included shale volume, porosity and permeability log derivation with the regression equation of porosity-permeability crossplot. In reservoir characterization, it is mainly based on analogue studies and Vsh and porosity log based on the concept of increasing clay away from channel. It yield a static model with facies model mainly channel trend feeding in reservoir sand, lithofacies model with rock type found in core description with distinct porosity ranges from 7.59% to 12.55 while permeability model with the regression equation interpreted in the crossplot giving good relationship between porosity and permeability in the model. Key aspect of this project is that the built a Chang 3 static model that can be serve as an input for dynamic model for flow simulation and as well as for further reservoir evaluation mainly volume assessment in Chang 3 area.